Return to work after COVID-19: an international perspective. Issue 1 (2nd January 2023) - Asaba, Eric; Sy, Michael; Pineda, Roi Charles; Aldrich, Rebecca; Anzai, Tetsuya; Bontje, Peter; Bratun, Urša; Farias, Lisette; Kapanadze, Maria; Šuc, Lea; Åkesson, Elisabet
ABSTRACT: Among individuals who have recovered from COVID-19 around the world, there is a substantial number who would need support in finding their way back to meaningful and productive work. The aims of this paper are to demonstrate the multitude of factors that shape return to work (RTW) practices across and within several countries, and argue for the need to explore RTW from an international perspective during an on-going pandemic, focusing on working age adults who have recovered from COVID-19. Conditions for RTW differ across countries. Occupational therapy has a central role in medical rehabilitation after injury and illness (including COVID-19), but the occupational therapy community has, to the best of our knowledge, yet to raise awareness and advance evidence regarding its role in post-COVID RTW processes. A robust evidence-based knowledge on RTW that can be utilised by occupational therapists during the present and future pandemics is needed.